2017
DOI: 10.3389/fnbeh.2017.00095
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ethanol-Metabolizing Enzymes by Developmental Lead Exposure: Effects in Voluntary Ethanol Consumption

Abstract: This review article provides evidence of the impact of the environmental contaminant lead (Pb) on the pattern of the motivational effects of ethanol (EtOH). To find a mechanism that explains this interaction, the focus of this review article is on central EtOH metabolism and the participating enzymes, as key factors in the modulation of brain acetaldehyde (ACD) accumulation and resulting effect on EtOH intake. Catalase (CAT) seems a good candidate for the shared mechanism between Pb and EtOH due to both its an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Although most of its industrial applications have been banned or are strictly regulated, lead (Pb) is still considered a public health concern due to its persistence in the environment globally. Several evidences indicate that developmental Pb exposure induces cognitive impairment, behavioral disturbances, and an altered response to drugs, including ethanol, both in children and laboratory animals (Mason et al, 2014;Virgolini et al, 2017). The stimulant and/or motivational responses to ethanol have been attributed to acetaldehyde (ACD), a metabolite generated in the brain primarily by the action of catalase (CAT), an enzyme of minor importance in liver ethanol metabolism Gill et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of its industrial applications have been banned or are strictly regulated, lead (Pb) is still considered a public health concern due to its persistence in the environment globally. Several evidences indicate that developmental Pb exposure induces cognitive impairment, behavioral disturbances, and an altered response to drugs, including ethanol, both in children and laboratory animals (Mason et al, 2014;Virgolini et al, 2017). The stimulant and/or motivational responses to ethanol have been attributed to acetaldehyde (ACD), a metabolite generated in the brain primarily by the action of catalase (CAT), an enzyme of minor importance in liver ethanol metabolism Gill et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Pb itself increases both, CAT activity and several EtOH responses when administered either acutely to adult animals (Correa et al, 1999b), or chronically to developmental rats (Valenzuela et al, 1989;Mattalloni et al, 2013) or chickens (Somashekaraiah et al, 1992). Interestingly, we have demonstrated that pharmacological (Mattalloni et al, 2013) or molecular (Mattalloni et al, 2019) manipulations of this enzyme have a direct impact on CAT activity and voluntary EtOH intake in developmentally Pb-exposed rats (reviewed in Virgolini et al, 2017). Similarly, CAT inhibition with specific antagonists such as 3-amino 1,2,4-triazole (AT) or sodium azide reduced both EtOH-induced locomotor activity (Sanchis-Segura et al, 1999;Correa et al, 2001) and the drug's anxiolytic responses (Correa et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…Although several industrial applications have been banned or restricted, neurobehavioral alterations are still reported in environmentally-Pb-exposed children. Experimental evidences in rodents indicate an enhanced vulnerability to the stimulating and motivational effects of ethanol (EtOH) as result of Pb exposure (Nation et al, 1986;Correa et al, 1999a;Virgolini et al, 2017). Since brain acetaldehyde accumulation is considered a key component of these responses (Aragon and Amit, 1985;Quertemont et al, 2005;Israel et al, 2015), EtOH metabolism emerged as an important aspect to consider when evaluating the mechanism that underlies the Pb-EtOH interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also consumed more EtOH than their respective controls and presented enhanced locomotor activity after the last voluntary consumption session ( Mattalloni et al, 2013 ; Mattalloni et al, 2017 ). As with worms, we ascribed these effects to differences in the activity of the enzymes involved in EtOH oxidation (results not shown, reviewed in Virgolini et al, 2017 ) and their interrelation with oxidative stress ( Virgolini et al, 2019 ), although the participation of the DAergic system was not assessed and thus cannot be discarded. Thus, despite the differences in the experimental design and animal model used in these approaches, we observed in both cases enhanced stimulant and motivational responses to EtOH as a consequence of early-life Pb exposure.…”
Section: Introductionmentioning
confidence: 99%